The Effectiveness of The Agricultural Investment Environment in Supporting the Production of Strategic Crops in Iraq for The Period From 2003-2021 - Imran Musa *, Salman; Kareem Brehy , Faris (Journal of Economics and Administrative Sciences, 2024)
Maximizing the effectiveness of the agricultural investment environment for all its basic inputs from the economic and human resources available in Iraq represents a qualitative breakthrough in the production of strategic crops, therefore, the research problem came from the weak production of strategic agricultural crops in Iraq in quantity and quality, due to the ineffectiveness of the agricultural investment environment, as a result of the lack of government support, the deterioration of the infrastructure of the agricultural sector, and a shortage of monetary capital, Finally, the scarcity of water resources, the problem was treated using the analytical method, thus, the research aims to demonstrate the importance of developing the agricultural investment environment and increasing government support and its impact on the production of strategic agricultural crops, the research concluded that Iraq possesses most of the basic inputs to the agricultural investment environment, but it lacks efficient management and optimal use, in addition to climate change, which has helped increase drought and desertification, the research also concluded that agricultural policy in Iraq includes obliging the investor to an agricultural plan in which the cultivated area is determined under the pretext of limited the capacity of the stores and the amount of strategic water storage despite Iraq’s need for strategic crops and thus the state’s attempt to meet the increasing demand for strategic crops t-hrough imports, which makes Iraq subject to the fluctuations of the global market and the depletion of hard currency, the researcher recommends efficient and optimal exploitation of natural, financial and human resources and keeping pace with scientific and technological progress in the production of strategic crops. In conclusion, the research included the deductive approach through the method of analytical description to advance the agricultural investment environment in Iraq.           Paper type: Research paper.